Does body mass index impact on the relationship between systolic blood pressure and cardiovascular disease?: Meta-analysis of 419 488 individuals from the Asia pacific cohort studies collaboration - Tsukinoki, R.; Murakami, Y.; Huxley, Rachel; Ohkubo, T.; Fang, X.; Suh, I.; Ueshima, H.; Lam, T.; Woodward, M. (2012)
Background and Purpose-: Elevated blood pressure and excess body mass index (BMI) are established risk factors for cardiovascular disease (CVD) but controversy exists as to whether, and how, they interact. Methods-: The interactions between systolic blood pressure and BMI on coronary heart disease, ischemic and hemorrhagic stroke and CVD were examined using data from 419 448 participants (=30 years) in the Asia-Pacific region. BMI was categorized into 5 groups, using standard criteria, and systolic blood pressure was analyzed both as a categorical and continuous variable. Cox proportional hazard models, stratified by sex and study, were used to estimate hazard ratios, adjusting for age and smoking and the interaction was assessed by likelihood ratio tests. Results-: During 2.6 million person-years of follow-up, there were 10 877 CVD events. Risks of CVD and subtypes increased monotonically with increasing systolic blood pressure in all BMI subgroups. There was some evidence of a decreasing hazard ratio, per additional 10 mm Hg systolic blood pressure, with increasing BMI, but the differences, although significant, are unlikely to be of clinical relevance. The hazard ratio for CVD was 1.34 (95% CI, 1.32-1.36) overall with individual hazard ratios ranging between 1.28 and 1.36 across all BMI groups. For coronary heart disease, ischemic stroke, and hemorrhagic stroke, the overall hazard ratios per 10 mm Hg systolic blood pressure were 1.24, 1.46, and 1.65, respectively. Conclusions-: Increased blood pressure is an important determinant of CVD risk irrespective of BMI. Although its effect tends to be weaker in people with relatively high BMI, the difference is not sufficiently great to warrant alterations to existing guidelines. © 2012 American Heart Association, Inc.